28. SOCIAL SUPPORT AND ITS RELATED FACTORS AMONG CANCER PATIENTS AT ONCOLOGY CENTER OF HUE CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Cancer is a chronic disease that affects all aspects of a patient's and family's life such as physical, psychological, social impacts, and requires continuous and prolonged care needs.Objectives: To describe the characteristics of social support and identify related factors in cancer patients undergoing treatment at the Oncology center of Hue Central Hospital.Methods: A cross-sectional descriptive study was conducted on 253 patients diagnosed with cancer at the Oncology center of Hue Central Hospital. The Medical Outcomes Study - Social Support Survey (MOS-SSS) scale measured the patients' social support characteristics on 4 dimensions: Tangible support, emotional-informational support, affectionate support, and social interaction.Results: The mean age was 56.62; gastrointestinal cancer had the highest incidence (21.3%); and 45.6% of patients were undergoing chemotherapy. The mean score for overall social support was 56.95; comprising 4 dimensions of tangible support, emotional-informational support, affectionate support, and social interaction were 71.07, 54.56, 65.02, and 37.28, respectively. Four significant factors related to overall social support scores were education level, marital status, occupation and self-quality of life.Conclusion: Social support remains inadequate for cancer patients, particularly in terms of social interaction. Interventions should prioritize patients with a low education group; adverse marriage, manual labor group, and patients with low quality of life.
Keywords: Social support; MOS-SSS scale; cancer patients